Beberapa Faktor yang Berhubungan dengan Kontaminasi Mikroorganisme pada Jamu Gendong Di Kota Semarang - Sulistiyani Sulistiyani; Siti Thomas Zulaikhah (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2006)
The objective of this study was to know some factors related to microbial contamination in herbal medicine products at Semarang City. This study was conducted by descriptive method employing cross sectional design in which samples were taken by purposive random sampling. The results showed that Escherichia coli, Salmonella, Staphylococcus aureus, Pseudomonas aeruginosa were identified. The number of fungi exceeded the standard indicating that 62.5% of the herbal medicines surveyed did not meet the required standard of Kepmenkes no. 661/Menkes/SK/VII/1994. The relationship between the quality of herbal row material, processing, and serving to the microbial contamination in herbal medicine products was observed.